2010
DOI: 10.1007/s11258-010-9781-2
|View full text |Cite
|
Sign up to set email alerts
|

Mid-successional stand dynamics in a cool-temperate conifer-hardwood forest in northern Japan

Abstract: Stand dynamics was studied over 13 years in a cool-temperate conifer-hardwood forest, northern Japan. A total 30 hardwood species and one conifer, Abies sachalinensis, larger than 1.5 cm DBH were recorded. The total stand density was 1677 trees ha -1 at the beginning, decreasing to 1184 trees ha -1 (30% reduction) over the study period, but the total stand basal area was almost unchanged (about 49 m 2 ha -1 ). This large reduction in total density was mainly due to the death of saplings and infrequent recruitm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Many long‐term forest observational studies reported that mortality exceeds recruitment rates and that forest stands develop with reduced tree density, especially for early successional species (Abrams & Nowacki, ; Harcombe et al., ; Leak & Smith, ; Takahashi, 2010a; Vepakomma, Kneeshaw, & St‐Onge, ). This is also true in the forest stand examined in this study, that is, the total basal area increased, accompanied with reduced tree density, during 13 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many long‐term forest observational studies reported that mortality exceeds recruitment rates and that forest stands develop with reduced tree density, especially for early successional species (Abrams & Nowacki, ; Harcombe et al., ; Leak & Smith, ; Takahashi, 2010a; Vepakomma, Kneeshaw, & St‐Onge, ). This is also true in the forest stand examined in this study, that is, the total basal area increased, accompanied with reduced tree density, during 13 years.…”
Section: Discussionmentioning
confidence: 99%
“…It is no doubt that disturbance is important to maintain species diversity (Pickett, ). Especially, in forest ecosystems with developed stratification, seedling establishment and population growth rates of shade‐intolerant species gradually decrease with stand development (Takahashi, 2010a; Takahashi, Yogo, & Ishibashi, ). However, shade‐intolerant species can dominate immediately from newly established seedlings after large disturbances because of high growth rates in bright conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The forest was well reserved, and therefore, there were no anthropogenic effects on the vegetation. Takahashi [21] described the vegetation and stand structure of this forest.…”
Section: Study Sitementioning
confidence: 99%
“…Schm. dominate in a cool-temperate conifer-hardwood mixed forest in northern Japan [21]. This study analyzes the population structure and dynamics of the four most dominant species based on size structure, gap regeneration and tree competition by using the 10-year data of permanent plots to examine how regeneration traits differ among the four most dominant species.…”
mentioning
confidence: 99%
“…These two different groups of species differ with respect to parameters such as seed traits and seedling size, and consequently exhibit different growth rates and survival success (Hewitt ; Poorter et al. ; Takahashi ). Furthermore, the risk of browsing and consumption (i.e.…”
Section: Introductionmentioning
confidence: 99%